“There Is Nothing I Cannot Achieve”: Empowering Latin American Women Through Agricultural Education - Gibbons, Judith L.; Eguigure-Fonseca, Zelenia; Maier-Acosta, Ana; Menjivar-Flores, Gladys Elizabeth; Vejarano-Moreno, Ivanna; Alemán-Sierra, Alexandra (Frontiers in Psychology, 2022)
Higher education, a key driver of women’s empowerment, is still segregated by gender across the world. Agricultural higher education is a field that is male-dominated, even though internationally women play a large role in agricultural production. The purpose of this study was to understand the experience, including challenges and coping strategies, of women from 10 Latin American countries attending an agricultural university in Latin America. The participants were 28 women students with a mean age of 20.9 ±1.8 years. Following informed consent and assurance of confidentiality, four focus group sessions (one for each year of study with a mean duration of 81 minutes) were conducted in Spanish. The central question was, “what has been your experience at the university?” Sessions were recorded and transcribed. Thematic coding was performed independently by two teams of researchers (from Latin America and North America), with the resulting schemas combined through mutual discussion. Member checking, auditing, and reflexivity contributed to trustworthiness of the process. Students reported that the personal qualities needed for success included determination, persistence, and self-efficacy. Many described an empowerment process, including increased discipline and self-efficacy from the first to fourth year of study. University life encompassed six themes: university structure and discipline (part of the ecosystem), two supportive microsystems (friends and classmates and institutional support) as well as three challenges (academic, peers, and machismo). Cultural influences instantiated in students’ daily experiences included familism, machismo, and religious faith. Students anticipated futures involving further education and contributions to society. We conclude that higher education in agriculture can serve as an effective means of empowering women to feed the world.